Match running performance and success across a season in German Bundesliga soccer teams - Hoppe, M. W.; Slomka, M.; Baumgart, C.; Weber, H.; Freiwald, J. (International Journal of Sports Medicine, 2015)
The aim of the study was to quantify the association between match running performance and success across a season in soccer teams competing within a European top league. We analyzed the match running performance data of all soccer teams from the German Bundesliga across the season 2012/13 (306 matches). The following match running performance data were used: total distance covered as well as number of running activities>18.0 km/h and > 22.7?km/h. Depending on the team`s ball possession status, all match running performance data were also analyzed as those with and without ball possession. The success across the season was defined as the final competition points accumulated. The match running performance alone was not significantly correlated with the final points accumulated (best r=0.24; p=0.34). In contrast, positive-significant correlations were observed for the match running performance with ball possession (best r=0.77; p<0.01). However, of these latter correlations, only the total distance covered with ball possession was a significant predictor (p<0.01) and accounted for 60% of the variance (R2=0.60) in the final points accumulated. It is concluded that it is not the match running performance alone that is important for achieving success in German Bundesliga soccer teams, but rather its relation to technical/tactical skills with respect to ball possession.